2010
DOI: 10.5194/hess-14-2355-2010
|View full text |Cite
|
Sign up to set email alerts
|

An inversion method based on multi-angular approaches for estimating bare soil surface parameters from RADARSAT-1

Abstract: Abstract. The radar signal recorded by earth observation (EO) satellites is sensitive to soil moisture and surface roughness, which both influence the onset of runoff.This paper focuses on inversion of these parameters using a multi-angular approach based on RADARSAT-1 data with incidence angles of 35 • and 47 • (in mode S3 and S7). This inversion was performed with three backscatter models: Geometrical Optics Model (GOM), Oh Model (OM), and Modified Dubois Model (MDM), which were compared to obtain the best c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
(52 reference statements)
0
23
0
Order By: Relevance
“…It should be noted that for each model there are some restrictions to use. For each model there are some validity range which are presented in different researches such as Dubois et al [1995], Ulaby et al [1981], Sahebi et al [2002], and Sahebi et al [2010].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that for each model there are some restrictions to use. For each model there are some validity range which are presented in different researches such as Dubois et al [1995], Ulaby et al [1981], Sahebi et al [2002], and Sahebi et al [2010].…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate dielectric constant and roughness using the Dubois model, the inverse model was used [Sahebi and Angles, 2010]. These two parameters were also calculated using the Oh model and iteration [Oh et al, 1992].…”
Section: Soil Surface Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…For high incidence angles and rough surfaces, the Oh model accurately estimated backscatter for the co-polarization ratio ) and for all polarizations at C band using RADARSAT data (Álvarez-Mozos et al, 2007). In contrast, some studies have found that the Oh model tends to overestimate radar backscatter for the crosspolarization or all polarizations (Merzouki et al, 2010;van Oevelen and Hoekman, 1999), whereas many others have found it tends to underestimate observed backscatter (Boisvert et al, 1997;Gherboudj et al, 2009Gherboudj et al, , 2011Merzouki et al, 2011;Sahebi and Angles, 2010). It was noted by several authors that the bias in the Oh model for a specific study area could be accounted for by applying a correction factor De Roo et al, 2001;D'Urso and Minacapilli, 2006;Merzouki et al, 2010), although more work is required to develop correction factors to operationally implement the Oh model for soil moisture retrieval (Merzouki et al, 2010).…”
Section: Backscattering Modelsmentioning
confidence: 98%
“…The original Dubois model needs HH and VV polarization SAR data as inputs to estimate soil moisture content. Sahebi and Angles [26] developed the Dubois model to estimate soil moisture content based on single polarization SAR data with two incidence angles. In this study, the modified Dubois model based on multi-band SAR data was developed and used to estimate soil moisture content independent of surface roughness.…”
Section: Modified Dubois Model Experimentsmentioning
confidence: 99%